Perceived COVID-19 stress and online aggression among Chinese first-year college students: a moderated mediation model - Guo, Lingjing; Xu, Liyuan; Yang, Qiang (Frontiers in Psychiatry, 2023)
Few studies have explored factors that may account for potential mechanisms between perceived coronavirus disease 2019 (COVID-19) stress and online aggression. The current study examined a moderated mediation model with anxiety as a mediator and perceived anonymity as a moderator. Data were collected from 3,069 participants across China. Participants completed scales assessing perceived COVID-19 stress, anxiety, online aggression, and perceived anonymity. Results suggested a significant indirect relationship between perceived COVID-19 stress and online aggression via anxiety. Moderating analyses revealed that perceived anonymity moderated the direct pathway and the second half of the indirect pathway of perceived COVID-19 stress and online aggression.